2011
DOI: 10.1111/j.1365-2222.2011.03879.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of vitamin D and antimicrobial peptide production during late‐phase allergic responses in the lung

Abstract: Levels of vitamin D metabolites, particularly 1,25(OH)(2)D, were low within the airways and increased after allergen challenge. The increases correlated with the magnitude of inflammation and increases in cathelicidin. Normalization to albumin suggested plasma exudation as a mechanism for the increases. The findings support a role for vitamin D in allergic and innate immune responses in the lung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 37 publications
1
26
1
Order By: Relevance
“…We also demonstrate for the first time that the Th2 cytokine IL-13 increases vitamin D-induced expression of hCAP18/LL-37, most likely by increasing expression of the 25D 3 -activating CYP27B1. A recent study by Liu et al reported increased levels of LL-37, 1,25D3, and 25D3 in bronchoalveolar lavage (BAL) fluid from allergic subjects after segmental allergen challenge, which is in line with our observations (32). However, their observations could be partly explained by vascular leakage.…”
Section: Discussioncontrasting
confidence: 34%
“…We also demonstrate for the first time that the Th2 cytokine IL-13 increases vitamin D-induced expression of hCAP18/LL-37, most likely by increasing expression of the 25D 3 -activating CYP27B1. A recent study by Liu et al reported increased levels of LL-37, 1,25D3, and 25D3 in bronchoalveolar lavage (BAL) fluid from allergic subjects after segmental allergen challenge, which is in line with our observations (32). However, their observations could be partly explained by vascular leakage.…”
Section: Discussioncontrasting
confidence: 34%
“…There may be several other explanations for our differing observations. First, few data exist regarding the relationship between plasma and sputum cathelicidin [25], [26]. Second, prior studies have focused on patient populations with specific exposures, such as farmers, patients with cystic fibrosis, or smokers in acute care facilities [22], [23].…”
Section: Discussionmentioning
confidence: 99%
“…Our study did not have concurrent blood and bronchoalveolar cathelicidin measurements. Prior data reported an association between peripheral blood and BAL cathelicidin levels [25]. Multivitamin use was self-reported and is therefore subject to expectation and recall bias.…”
Section: Discussionmentioning
confidence: 99%
“…There has been considerable interest in recent years in the potential role of vitamin D deficiency as a risk factor for a host of conditions including asthma and other allergic diseases [3][4][5]. We have recently reviewed this controversial literature and a potential role in food allergy is postulated in a review by Vuillermin and colleagues (pp.…”
Section: Vitamin D; the New Wonder Drug?mentioning
confidence: 99%